Anti-Müllerian Hormone Levels as Predictor of In Vitro Fertilization Outcomes - Mila Maidarti; Prini Diandara Garinasih; Aprilia Asthasari Siregar; Gita Pratama; Achmad Kemal Harzif; Kanadi Sumapraja; Budi Wiweko (Faculty of Medicine Universitas Indonesia, 2021)
A decrease in serum anti-müllerian hormone (AMH) concentration suggests the reduction of antral follicle number. AMH serum level was correlated with ovarian stimulation outcomes, oocyte quantity and quality, embryo quality and in vitro fertilization (IVF) outcomes. However, the use of AMH to predict pregnancy rates in IVF is still debatable. This study aimed to determine the role of AMH in predicting ovarian response and pregnancy rates in IVF programs. This was a retrospective cohort study involving patients who underwent a short protocol of ovarian stimulation for IVF at the Yasmin clinic, dr Cipto Mangunkusumo General Hospital. from March 2013 to March 2021. A total of 1,527 out of 3,880 IVF cycles were included. Poor ovarian response was determined as a collection of fewer than four oocytes following ovarian stimulation. The data was then analyzed using the Mann Whitney test if the data distribution was not normal or the unpaired t-test if the data distribution was normal. Median AMH levels were higher in the normal (2.5(0.01-32)) compared to poor responder (0.68(0.01-6.86)) group (p<0.05; Mann Whitney). Serum AMH level and age had predictive value for pregnancy rate (p<0.05; Mann Whitney). Keywords: AMH, ovarian response, pregnancy rate, IVF. Kadar Hormon Anti-Müllerian sebagai Prediktor Luaran Fertilisasi in Vitro Abstrak Penurunan konsentrasi serum hormon anti-müllerian (HAM) menunjukkan penurunan jumlah folikel antral. HAM serum berkorelasi dengan luaran stimulasi ovarium kuantitas dan kualitas oosit serta kualitas embrio dan luaran fertilisasi in vitro (FIV). Namun, penggunaan HAM untuk memprediksi angka kehamilan dengan stimulasi ovarium pada FIV masih diperdebatkan. Tujuan penelitian ini untuk mengetahui peran serum HAM dalam memprediksi respons ovarium dan laju kehamilan pada program FIV. Penelitian ini adalah studi kohort retrospektif yang melibatkan pasien yang menjalani protokol singkat stimulasi ovarium pada program FIV di klinik Yasmin rumah sakit dr Cipto Mangunkusumo.dari bulan Maret 2013 sampai Maret 2021. Sebanyak 1.527 dari 3880 siklus IVF dimasukkan ke dalam penelitian. Dikatakan perespon buruk apabila diperoleh kurang dari empat oosit setelah stimulasi ovarium. Data kemudian dianalisis dengan menggunakan uji Mann Whitney bila sebaran data tidak normal atau uji t tidak berpasangan bila sebaran data normal. Median kadar HAM lebih tinggi pada kelompok perespons baik (2.5 (0.01-32)) dibandingkan perespons buruk (0.68 (0.01-6.86)) (p<0,05; Mann Whitney). Kadar HAM serum dan usia memiliki nilai prediktif terhadap angka kehamilan (p<0,05; Mann Whitney). Kata kunci: hormon anti-Müllerian, respons ovarium, angka kehamilan, FIV.